3T Magnetic Resonance Imaging of the Wrist Tendons. Issue 5 (October 2020) - Rehwald, Christine; Joyce, Ryan P.; Pezeshk, Parham; Del Grande, Filippo; Khoshpouri, Parisa; Chew, Felix; Chalian, Majid
Abstract : Abstract: Magnetic resonance imaging (MRI) is frequently used in the imaging evaluation of wrist pain. The complex anatomy of the wrist can be demonstrated by MRI. Three tesla (3 T) MRI offers increased signal-to-noise ratio relative to 1.5 T MRI allowing for higher soft tissue contrast and better spatial resolution. The resulting increase in conspicuity of fine anatomic detail may improve the detection and characterization of wrist pathology. In this article, we will review the anatomy, normal variants, and common pathologies of the wrist tendons as evaluated on 3 T MRI.